Navigating the complexities: assessing governance mechanisms for inter-regional cooperation - Mahardhani, Ardhana Januar (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This article will explain further the inter-regional governance cooperation required by regions that touch each other, as well as by regions that have similar areas and natural products. Cooperation is needed to meet the needs of a region that cannot be met alone and therefore requires assistance from other regions. This article uses examples of successful collaboration carried out by the East Java Provincial Government where there are several good collaborations that will be and are currently being carried out. The method used in this writing is literature study by analyzing previous research that has been carried out and then analyzing it with appropriate theory to arrive at conclusions that are in line with what was expected. The results in this paper are that in the process of cooperation, commitment from each region is very much needed, there must be an official written agreement to enter into a collaboration. In developments in the field it is also known that in implementing cooperation there is a need for other actors who are interconnected. The conclusion in this paper is that in managing cooperation, each region must have principles that must be upheld, for example in implementing cooperation in East Java Province which uses Mintzberg principles, then in implementing cooperation it will use Mintzberg principles. It also involves other elements which in this case are known as the pentahelix concept.